Stochastic method for determining the coherence length of a TEA CO2 laser - Codnia, Jorge (2013)
In this work the results of the measurement of the coherence length of a TEA CO2 laser developed in DEILAP are presented. A Michelson interferometer of about 5 m of optical path length difference was built for this purpose. A motorized translation optical mount was placed in one arm in order to enable the variation of the optical path length in many wavelengths. The length of the other arm was varied manually in steps of several tens of centimeters. Spatial filtering forced the laser to oscillate in a single transverse mode, TEM00. An innovative stochastic technique for data analysis allowed determining the amount of longitudinal modes, the amplitude and the individual average coherence length of each mode as well as the global coherence length of the laser. This technique was later compared with a method based on the analysis of the Fourier transform of the time series obtained at the interferometer input.